A virtual roundtable on Iser’s legacy Part II: conversation with Mark Freeman (ENTHYMEMA, 2017)
In this article you find the second part of a roundtable on Wolfgang’s Iser legacy with Gerald Prince, Mark Freeman, Marco Caracciolo and Federico Bertoni. In Part II we discuss with Prof. Mark Freem the role of narrative hermeneutics in understanding the human realm and the tenets of self-interpretation, as well as the necessity of literary antrhopology and literary theory.
Keywords: Narrative hermeneutics; narrative psychology; Ricoeur; self-interpretation; narrative studies